Rhetorical Strategies in Qur'anic Theological Debates: A Hermeneutical Analysis - Nabrisah, Zulfan; Aminullah El-Hady; Abdul Rokhim (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
Studies on debate verses in the Qur’an have generally focused on linguistic aspects, thematic interpretation, or the ethics of dialogue, while relatively few have specifically examined the rhetorical strategies employed in theological debates through a thematic-hermeneutical approach. This study aims to analyze the rhetorical strategies of theological debate verses in the Qur’an by tracing the lexical roots of jadala, ḥāja, and khaṣama, and subsequently interpreting them through Fazlur Rahman’s double movement hermeneutics. Employing a qualitative descriptive-analytical method, this research integrates thematic Quranic Tafsir and hermeneutical approaches. The data were analyzed through verse identification, thematic contextual analysis, mapping of rhetorical forms, and contextualization of their universal values in relation to contemporary communication challenges. The findings reveal twenty-three verses that contain theological debates. The rhetorical strategies identified include rational argumentation, rhetorical questioning, negative labeling, affirmation of prophethood, descriptions of consequences, semantic contrasts, and historical narratives. Through the lens of Fazlur Rahman’s hermeneutics, the study formulates three universal principles: rational coherence, the cultivation of ethical consciousness, and communicative integrity. The novelty of this research lies in its integration of rhetorical analysis, thematic Quranic Tafsir, and double-movement hermeneutics to examine verses of theological debate. Its contribution is the development of an ethical-rhetorical framework for religious communication in the digital age, particularly in addressing skepticism, disinformation, emotional manipulation, and the crisis of public trust.